The electronic chart – Present status and future problems - Kerr, A. J.; Eaton, R. M.; Anderson, N. M. (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1986 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Kerr, A. J., Eaton, R. M., and Anderson, N. M. (1986). The electronic chart – Present status and future problems. The International Hydrographic Review, 63(1), 97–105. https://journals.lib.unb.ca/index.php/ihr/article/view/23424 This paper was presented at the Fifth International Congress of the International Association of Institutes of Navigation, Tokyo, Japan, October 1985. It is published in the Journal of Navigation (U.K.), Vol. 39, No. I, 1986 and reproduced here with permission.